PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA, DAN KESADARAN MEREK TERHADAP KEPUASAN PELANGGAN PENGGUNA JASA TRANSPORTASI OJEK ONLINE (Studi Pada Pelanggan Go-Jek Dan Grab Di SMK Trisakti Bandar Lampung) - Wuryanti, Lestari; Ferani, Ferani (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2018)
AbstractThis study aims to analyze the customer satisfaction of users of ojek transportation services onlineabout the influence of service quality, price perception, and brand awareness. The population of thisstudy consists of 289 students at SMK Trisakti Bandar Lampung. A qualified questionnaire was 168respondents. Data collection using questionnaire. Analysis of data using SmartPLS analysis tool 3.The results showed a positive influence between service quality, price perceptions and brandawareness of customer satisfaction of users of ojek transportation service Online at SMK TrisaktiBandar Lampung.